Effect and Strategy of 1-stage Interrupted 2-level Transpedicular Wedge Osteotomy for Correcting Severe Kyphotic Deformities in Ankylosing Spondylitis. Issue 4 (May 2017) - Zhao, Yongfei; Wang, Yan; Wang, Zheng; Zhang, Xuesong; Mao, Keya; Zhang, Yonggang
Abstract : Study Design: Prospective study. Objective: To investigate the safety, outcome, and strategy of the 1-stage interrupted 2-level transpedicular wedge osteotomy for correcting the severe kyphotic deformity in ankylosing spondylitis (AS). Summary of Background Data: There has been a large series in the literature reporting on results of osteotomy for the correction of kyphotic deformity secondary to AS. However, few articles have reported, in detail, the plan, design, strategy, and effect of 1-stage interrupted 2-level transpedicular wedge osteotomy for the correction of severe kyphotic deformity in AS. Materials and Methods: From May 2003 to February 2010, 24 consecutive patients, 17 males and 7 females, suffering from AS with severe spinal kyphosis, underwent 1-stage interrupted 2-level transpedicular wedge osteotomy in our hospital by the corresponding author. Improvements in relevant parameters were recorded and clinical results were evaluated. Results: The average operating time was 282±43 minutes, and the average blood loss was 2202±737 mL. All the global and regional spinal alignments improved to relatively normal status: the global thoracolumbar kyphosis angle improved from 101.5±10.8 to 24.8±5.8 degrees ( P <0.001), the thoracolumbar kyphosis improved from 37.9±5.1 to 0.7±12.8 degrees ( P <0.001), and the lumbar lordosis improved from 35.0±9.2 to −25.7±10.9 degrees ( P <0.001). Meanwhile, the chin-brow vertical angle improved from 79.5±5.1 to 8.5±2.7 degrees ( P <0.001), and the sagittal imbalance distance improved from 49.6±6.5 to 11.5±3.5 cm ( P <0.001). All the patients could walk with horizontal vision and lie on their backs postoperatively, and scoliosis research society-22 scores improved from 1.6±0.2 preoperatively to 4.3±0.2 at the 2-year follow-up. The mean time of follow-up was 52±28 months. Fusion of the osteotomy was achieved in each patient and no instances of loss of correction or implant failure were noted. Conclusion: For correcting severe kyphosis in patients with AS, the 1-stage interrupted 2-level transpedicular wedge osteotomy is a safe and effective technique that significantly improves appearance and function.